POLITIK IDENTITAS AGAMA LOKAL Studi tentang Aliran Kepercayaan Perjalanan Ciparay Bandung - Asep Lukman Hamid (Fakultas Agama Islam Universitas Wiralodra, 2018)
Indonesia is one of the most pluralist countries. This plurality can be seen in terms of many religions, beliefs, ethnicities, cultures and languages. This reality on the one hand is very open possibility of potential tension and social conflict. On the other hand, if being able to manage it proportionally and professionally will grow into a force capable of bringing to a more meaningful life. This paper seeks to describe the good relationship between Muslims and followers of Aliran Kepercayaan Perjalanan. In social interaction between the two occurs symbiosis mutualism without any prejudice danger. This reality is interesting to examine in order to discover the factors that become the social glue between Muslims and the followers of Aliran Kepercayaan Perjalanan and to find the political practice of their identity. Based on the field survey found that one of the factors that become social glue is because upholding the values of delay as reflected in the expression of silih asih, silih asah, and silih asuh.